In vivo imaging of uterine cervix with a Mueller polarimetric colposcope - Vizet, Jérémy (Sci Rep, 2017)
Mueller polarimetric imaging enables the detection and quantification of modifications of the collagen fibers in the uterine cervix due to the development of a precancerous lesion. This information is not accessible through the use of the classic colposcope, a low magnification microscope used in current practice for cervical cancer screening. However, the in vivo application of Mueller polarimetric imaging poses an instrumental challenge: the device should be sufficiently compact, while still being able to perform fast and accurate acquisition of Mueller matrices in real-world conditions. In this study, the first wide field Mueller Polarimetric Colposcope (MPC) for the in vivo analysis of uterine cervix is presented. The MPC has been fabricated by grafting a miniaturized Mueller polarimetric imager on a classic colposcope. This new imaging tool performs the fast acquisition of Mueller polarimetric images, thus eliminating any blurring effects due to patient movements. It can be easily used by a practitioner with little change to their existing practice. Finally, the MPC was tested in vivo on a number of patients in the field.